CHANGES OF PERIODONTAL BLOOD SUPPLY IN PATIENTS WITH MAXILLOMANDIBULAR ANOMALIES AND DISORDERS OF THE ARCHITECTONICS OF THE VESTIBULE OF THE MOUTH - Makhlynets, N.P.; Ozhogan, Z.R.; Rozhko, M.M.; Prots, H.B.; Ilkiv, M.M. (World of Medicine and Biology, 2023)
We studied rheological changes in periodontal tissues in 60 patients 12–15 years old with maxillomandibular anomalies, deformities before treatment and after surgical correction. In comparison group where were 15 persons without maxillofacial anomalies, deformities, oral habits and periodontal status. The results showed the presence of blood circulation deficit and reduce the trophic tissue, which was indicated by the increase in vascular tone index, venous outflow index, peripheral resistance index and reduce of extensive blood flow index аnd rheographic index (p
Keywords: vestibule of the mouth; periodontium; oral mucosa; allogeneic transplantation; blood supply